Internet Addiction among Students in Oran's University Housing During COVID-19 Pandemic - hamri, sara (Journal of Social Sciences and Humanities, 2025)
This study aimed to investigate the prevalence of internet addiction among university students and its extent during the COVID-19 pandemic. It also sought to determine whether there were statistically significant differences in internet addiction based on gender and major. The total sample size was 156 students who use the internet and reside in Belkaid University Housing in Oran. A descriptive approach was adopted to achieve the research objectives, and Kimberly Young's Internet Addiction Test (1996) was used as a data collection tool. After statistical analysis of the data using appropriate statistical methods, the study yielded the following results: 1.A low level of internet addiction was found among the study sample. 2.There were statistically significant differences in internet addiction attributed to gender, with females showing higher levels of addiction. 3.There were no statistically significant differences in internet addiction attributed to major.